The Impact of Parental Relationship Satisfaction on Infant Development: Results From the Population-Based Cohort Study DREAM - Nicolaus, Caroline; Kress, Victoria; Kopp, Marie; Garthus-Niegel, Susan (Frontiers in Psychology, 2021)
Extensive literature has shown that interparental conflicts and violence have detrimental effects on children´s adjustment in childhood and adolescence. It is not equally well understood how parental relationship satisfaction impacts infant communicational and personal-social development during the first year of life. This longitudinal study examines (a) the impact of maternal and paternal relationship satisfaction on infant development, (b) whether this prospective association is mediated by parent-infant relationship, and (c) a potential moderating effect of infant gender. Data were derived from the population-based cohort study “Dresden Study on Parenting, Work, and Mental Health” (DREAM) including 1,013 mothers and 673 fathers. Relationship satisfaction and parent-infant relationship were assessed 8 weeks postpartum, infant communicational and personal-social development were measured 14 months postpartum. Multiple linear regression, mediation, and moderation analyses were conducted for mothers and fathers separately. It was shown that paternal relationship satisfaction was a significant predictor of infant personal-social development. This prospective association was mediated by father-infant relationship, but neither mitigated nor magnified by infant gender. A similar effect was not found in the mothers´ sample. Parental relationship satisfaction did not prove to be a significant predictor of infant communicational development in either mothers or fathers. The study findings highlight the importance of paternal relationship satisfaction and father-infant relationship for infant personal-social development. Appropriate prevention and intervention approaches are needed to strengthen the interparental relationship satisfaction and parent-infant relationship, especially among fathers.